High prevalence of cardiovascular co-morbidities in patients with symptomatic knee or hand osteoarthritis. (2nd January 2016) - Calvet, J; Orellana, C; Larrosa, M; Navarro, N; Chillarón, JJ; Pedro-Botet, J; Galisteo, C; García-Manrique, M; Gratacós, J
Abstract : Objectives : To evaluate the frequency of cardiovascular events (CVEs) and metabolic syndrome (MetS) in patients with symptomatic knee or hand osteoarthritis (OA). Method : A cross-sectional study conducted by rheumatologists in a primary care setting. Consecutive symptomatic patients with primary knee or hand OA were included and patients with soft tissue conditions served as the control group. Hypertension, diabetes mellitus, obesity, dyslipidaemia, and CVEs consisting of myocardial infarction, angina, or cerebrovascular disease were recorded. Results : A total of 254 OA patients (184 with knee OA and 70 with hand OA) and 254 control patients were included. The frequency of obesity was higher in all OA groups and hypertension was more frequent in knee OA. MetS was significantly more frequent in patients with OA as a whole group and in knee or hand OA groups separately (p < 0.001, p = 0.002, and p = 0.007, respectively, vs. control group), with odds ratio (OR) 2.4, 95% confidence interval (CI) 1.26–4.55 in the OA group, OR 2.29, 95% CI 1.15–4.54 in the knee OA group, and OR 2.67, 95% CI 1.15–6.19 in the hand OA group. A higher prevalence of CVEs in the three OA groups was observed compared with the control group. Conclusions : A high frequency of MetS and CVEs was observed in OA patients in a primary care setting.